STUDENTS’ MISCONCEPTIONS PROFILE IN CELL BIOPROCESS USING THREE-TIER DIAGNOSTIC TEST - Pratiwi, Rifanissa Eka; Raharjo, Raharjo (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2021)
Abstract Lack of conceptual comprehension can lead students to form a wrong concept. Students’ conceptual comprehension that is different from the actual concept is called a misconception. Biological topic that is prone to misconception is cell bioprocess because the topic is abstract and complete. This research aims to describe the profile of students’ misconceptions using the three-tier diagnostic test, to describe the factors that cause misconceptions, and to offer solutions that overcome students’ misconceptions in cell bioprocess topic. The data collection methods were carried out by providing a three-tier diagnostic test through google form and interviewing through google meet and social media. The research subjects were 60 students of the 11th grade MIPA in SMA Negeri 1 Kamal. The data of diagnostic test were processed and grouped according to the category of students’ conceptual comprehension, besides the interviews data were analyzed by generalizations based on interviews’ answers. The results showed that 76% misconception occurred in cell bioprocess with 79.40% misconception in membrane transport, 74.30% misconception in protein synthesis, and 71.80% misconception in cell reproduction. Factors that cause misconceptions are students' low mastery of the concepts, the use of complicated terms and incomplete information in textbooks, also the lack of interaction between teachers and students. Students’ misconceptions can be reduced through the application of interactive models or media that assist in constructing conceptual comprehension correctly. Further studies of the development and implementation of digital-based learning media in cell bioprocess topic including membrane transport, cell reproduction, and protein synthesis sub-topic should be done near the future to reduce students’ misconceptions. Keywords: misconception, cell bioprocess, three-tier diagnostic test